Optimalisasi Digital Marketing dan Inovasi Pelayanan Publik dalam Pengembangan Bank Pembangunan Daerah Jawa Tengah - Ade Sony Noverianto; Suparno Suparno; Indra Kertati (Jurnal Media Administrasi, 2025)
This research aims to analyze the optimization of digital marketing in increasing the competitiveness of Bank Jateng, formulate the main challenges in the implementation of digital-based public service innovations, and develop an integration strategy between digital marketing and public service innovation to strengthen the role of Bank Jateng in regional economic development. The research method used was descriptive qualitative with data collection techniques through interviews with 11 informants and distribution of questionnaires to 96 respondents. The results of the study show that digital marketing optimization is able to increase competitiveness through integrated strategies between divisions, increasing content creativity, and strengthening analytics systems for performance evaluation. However, the main challenges faced include the digital capability gap and the need to improve the quality of responsive services. The implementation of digital innovation is multidimensional, including internal coordination that is not optimal, limited product diversification, digital service gaps, and data management that has not been integrated. The strategy of integrating digital marketing and public services requires a holistic approach through organizational capacity building, financial performance optimization, market reach expansion, and continuous innovation. Collaboration between divisions and strong leadership is key in supporting financial inclusion and regional economic growth. This research provides strategic recommendations for Bank Jateng in facing the increasingly dynamic competition of the banking industry in the digital era.